Reimagining arts education: Empowering deaf learners through the visual-musical innovation of Gawang Angklung - Saprudin, Saprudin; Sukmayadi, Yudi; Julia, Julia; Milyartini, Rita (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2025)
This study examines the role of the Gawang Angklung (Galung) application, a visual-based digital tool integrating traditional angklung music with interactive visual cues, in supporting inclusive music education for deaf learners. Designed to bridge the gap between sound-based musical instruction and the learning needs of students with hearing impairments, Galung enables ensemble participation through synchronized visual signals. Using a convergent mixed-methods design, data were collected from 24 deaf students, four music educators, and two application developers through interviews, classroom observations, and questionnaires. Quantitative results showed significant improvements in rhythmic accuracy (p < .01) and tempo recognition, while qualitative analysis revealed increased motivation, collaborative engagement, and communicative confidence. The integration of Galung aligns with constructivist and aesthetic learning principles, offering a multisensory, culturally grounded approach to music instruction. Despite its benefits, challenges were identified, including teacher training needs and technical limitations. This study highlights the potential of culturally embedded, visually adaptive technologies to promote inclusivity, accessibility, and active participation in arts education, while contributing to the broader discourse on equitable learning opportunities for students with disabilities.